2008
DOI: 10.1111/j.1530-0277.2007.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol in a Social Context: Findings From Event‐Contingent Recording Studies of Everyday Social Interactions

Abstract: Alcohol consumption in a social context may have predominantly positive effects, an observation which is at odds with most alcohol-induced aggression experiments performed in laboratory settings. Drinking in everyday life may be less likely to result in aggression because, unlike in most laboratory experiments, individuals can choose among a variety of behaviors in response to social cues and the alcohol dose consumed is usually lower. Event-contingent recording provides a new approach for the study of alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
2
25
1
2
Order By: Relevance
“…Individuals who were rejected who also underwent a mindfulness intervention behaved with less hostility following the interaction (Heppner et al, 2008). Although this method for assessing interpersonal interactions has been previously used without detectable reactivity effects (aan het Rot et al, 2008; Russell et al, 2010; Roche et al, 2014), future research should examine whether self-monitoring of interpersonal behaviors results in differences in actual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who were rejected who also underwent a mindfulness intervention behaved with less hostility following the interaction (Heppner et al, 2008). Although this method for assessing interpersonal interactions has been previously used without detectable reactivity effects (aan het Rot et al, 2008; Russell et al, 2010; Roche et al, 2014), future research should examine whether self-monitoring of interpersonal behaviors results in differences in actual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Using event-contingent reporting of daily social in-FIGURE 2. Proportion of positive behavior observed as a function of actor and partner alcohol condition teractions, aan het Rot et al (2008) found increased ratings of agreeableness in participants' reports of their own and others' behavior when alcohol was involved compared with when it was not. Although alcohol effects emerged using coder ratings of behavior in our study, participants did not report differences in their own or partner's behavior according to alcohol condition, suggesting that behavioral effects were modest and outside of awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Young people report drinking in order to enhance their emotional experience in social settings, and these social motives are the most strongly endorsed reason for drinking alcohol (Cooper, Russell, Skinner, & Windle, 1992; Cooper, 1994). Recently, studies employing event-contingent recording confirm that everyday social interactions involving alcohol consumption are associated with positive mood and social affiliation and the alleviation of negative emotions (Aan Het Rot, Russell, Moskowitz, & Young, 2008; Armeli et al, 2003). …”
Section: Alcohol and Social-emotional Rewardmentioning
confidence: 99%